Smart and Sustainable Mobility: A Systematic Review of Industry 4.0 Applications in Automotive Sustainability, Alternative Fuels, and EV Charging Systems - Wagino Wagino; Mycel A. Capilayan; Muji Setiyo; Volodymyr Tymofiiv; Dwi Sudarno Putra; Dori Yuvenda; Rahmat Desman Koto (Universitas Muhammadiyah Magelang, 2025)
This systematic review analyzes the integration of Industry 4.0 technologies in sustainable manufacturing and clean energy technology within the automotive industry, focusing on electric vehicle infrastructure development and renewable energy implementation. Through a comprehensive analysis of 25 selected articles from 200 articles (10 sustainability articles, 12 alternative fuels, and 3 electric vehicle charging stations articles) published between 2018 and 2024, this study employs PRISMA methodology combined with bibliometric content and scientometric analysis. The review reveals significant temporal evolution in research focus, progressing from basic energy efficiency studies (2018-2020) to enhanced Industry 4.0 technology integration (2020-2022), culminating in strong convergence between renewable energy implementation, smart infrastructure development, and circular economy principles (2022-2024). Key findings highlight the critical role of AI, IoT, and blockchain in enabling sustainable manufacturing processes and smart grid integration for EV infrastructure. Integrating hybrid energy storage systems with clean energy technologies is crucial for addressing energy transition challenges and reducing fossil-fuel dependence. The study identifies research gaps in comprehensive methodological approaches integrating technical innovation, sustainable manufacturing, and climate action considerations, particularly in developing regions. Future research opportunities include machine learning applications for dynamic energy system optimization and innovative business models supporting sustainable technology implementation across various socio-economic contexts. This review contributes to understanding technology integration patterns in sustainable transportation systems. It provides strategic recommendations for researchers, industry practitioners, and policymakers in advancing low-carbon mobility solutions and resilient infrastructure development.